2017
DOI: 10.1063/1.4997175
|View full text |Cite
|
Sign up to set email alerts
|

Photoemission and photoionization time delays and rates

Abstract: Ionization and, in particular, ionization through the interaction with light play an important role in fundamental processes in physics, chemistry, and biology. In recent years, we have seen tremendous advances in our ability to measure the dynamics of photo-induced ionization in various systems in the gas, liquid, or solid phase. In this review, we will define the parameters used for quantifying these dynamics. We give a brief overview of some of the most important ionization processes and how to resolve the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 124 publications
(136 reference statements)
0
41
0
Order By: Relevance
“…Measurement techniques like reconstruction of attosecond beating by interference of two-photon transitions (RABBITT) [6][7][8][9][10] and attosecond streaking [11,12] have made the relative Wigner time-delays τ W [13] between different orbitals of atoms and molecules accessible. Several pioneering experiments [6,11,12] have employed isolated attosecond pulses (IAP) and attosecond pulse trains (APTs) to resolve photoemission time-delays [13][14][15][16][17][18][19][20][21][22][23] in atoms, molecules and solids.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement techniques like reconstruction of attosecond beating by interference of two-photon transitions (RABBITT) [6][7][8][9][10] and attosecond streaking [11,12] have made the relative Wigner time-delays τ W [13] between different orbitals of atoms and molecules accessible. Several pioneering experiments [6,11,12] have employed isolated attosecond pulses (IAP) and attosecond pulse trains (APTs) to resolve photoemission time-delays [13][14][15][16][17][18][19][20][21][22][23] in atoms, molecules and solids.…”
Section: Introductionmentioning
confidence: 99%
“…This contrasts with nonresonant time delays which are at the attosecond level. Thus, the time delays in the resonance region are about five orders of magnitude larger than nonresonant delays [10][11][12][13][16][17][18][19]; they are also considerably larger than the delays in the vicinity of a similar resonance in Ar [23].…”
Section: Resultsmentioning
confidence: 90%
“…An early review can be found in [9]. Later works are represented by [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Most of these investigations have involved nonresonant photoemission.…”
Section: Introductionmentioning
confidence: 99%
“…This effect is further enhanced by the wave itself, which tries to converge (push) its energy on to the stimulated dipole. The rationale behind the introduction of this push-pull postulate is supported by, first, (i) from the theoretical modeling of radiation field converging on a resonant dipole (see Fig.2, right diagram); second, (ii) from the observations in many fast and efficient resonance fluorescence experiments, which is quantified in Fig.3; third, (iii) from the observed transition time period for photoelectron release is always below a femtosecond [15]. We summarize this collective behavior of resonantly excited atoms as behaving like a large quantum cup, which absorb the necessary quantum of energy through co-operative pushpull mechanism.…”
Section: Accommodating Quantized Absorption Out Of Multiple Classicalmentioning
confidence: 99%